Real-time indoor positioning system for a smart workshop using white LEDs and a phase-difference-of-arrival approach - Du, Pengfei (2020)
In order to provide a cost-effective indoor positioning and tracking service for autonomous ground vehicles and other important assets in smart factories, we report the theory and experiments for a real-time indoor positioning system using commercially available LED lamps. Inspired by the fundamental theory of the global navigation satellite system, the proposed system uses the phase difference of arrival (PDOA) approach to obtain the time difference of arrival of each carrier transmitted from individual modified LED lamps so as to estimate the receiver position. A prototype of the atto-cellular positioning system covering an area of 2.2 × 1.8 m2 with a height of 2 m was designed and experimentally demonstrated. For the design, we performed a simulation based on the Crámer-Rao bound to achieve optimal LED lamp arrangement, RF power, and other parameters. Furthermore, a virtual local oscillator for the PDOA scheme was applied to reduce the hardware complexity and to ensure the processing speed. In the experiment, the receiver was mounted on a movable material buffer station in a smart workshop, and the positioning performance was validated by tracking the trajectory of the material buffer station moving within the positioning coverage area. The experimental results show that an average positioning accuracy of ∼7 cm was achieved.